DESCRIPTION OF CHILDREN'S THUMB SUCKING HABIT IN KINDERGARTEN CIMAHI TENGAH INDONESIA - Irsyad, Widya; EL Fitriyah, Rhabiah; Muzdalifah, Ifa (Fakultas Kedokteran Gigi Unjani, 2024)
Thumb sucking is one of the most common oral habits in children. Thumb sucking could cause interference with thecclusion and jaw malformations which could lead to permanent teeth eruption if the problem persists. Thumb sucking habit causes contractions on the buccal and lips. Thumb sucking habit is a habit that is done more frequently compared to other oral habits, especially in the first year after birth. Based on that, research was done to find a thumb-sucking habits scheme for children aged 4-5 years in kindergarten in Central Cimahi District. This research is a descriptive study with a cluster random sampling method. The data were analyzed descriptively in a total sample of 236 parents of children aged 4-5 years in kindergarten in Central Cimahi District. The results showed 14 children (5.93%) had a thumb-sucking habit, eight children (57.14%) 4-year-old, six children (42.86%) were aged five years, seven boys (50%) and seven girls (50%), 2 mm overjet was found in ten children (71.43%), duration of sucking <1 hour/day by seven children (50%), and the sucking condition while playing as many as six children (42.86%). The conclusion of the study is the incidence of the thumb-sucking habit in Cimahi District kindergarten is low; the majority of 4-year-old end the same, duration thumb-sucking habit <1 hour/day, with a distance of 2 mm and overjet is done during when they are playing around. DOI : 10.54052/jhds.v3n3.p239-248